Broadband‐Solubility Diketopyrrolopyrrole Derivative with Both Polar Cyano and Nonpolar Alkyl Groups for Stable Organic Photosensors and Diffusion‐Processed Organic Solar Cells. Issue 8 (17th June 2016) - Lee, Hyena; Han, Hyemi; Jeong, Jaehoon; Kim , Hwajeong; Song, Dong‐Ik; Kim, Youngkyoo
Abstract: A small‐molecular diketopyrrolopyrrole (DPP) derivative with cyano groups, (2E, 2′E)‐diethyl‐3, 3′‐((5, 5′‐(2, 5‐bis(2‐ethylhexyl)‐3, 6‐dioxo‐2, 3, 5, 6‐tetrahydropyrrolo[3, 4‐c]pyrrole‐1, 4‐diyl) bis(thiophene‐5, 2‐diyl))bis(4, 1‐phenylene)) bis (2‐cyanoacrylate) (EHTPPD‐ECPA), was synthesized via Suzuki‐coupling reaction. The synthesized EHTPPD‐ECPA exhibited a broadband solubility in both polar and nonpolar solvents due to the presence of both polar (cyano) and nonpolar (alkyl) groups. A bright pink photoluminescence (PL) was measured from EHTPPD‐ECPA solutions, whereas almost no PL was observed from the EHTPPD‐ECPA films because of high intermolecular stacking (band gap=1.7 eV). EHTPPD‐ECPA was found to act as an electron‐donating component in all‐small‐molecular bulk heterojunction layers for organic photosensors (photodetectors), while it played a critical role in improving the efficiency of diffusion‐processed polymer/fullerene solar cells with the mixed electron‐donating layers. Abstract : Broadband Solubility Molecule: Novel small‐molecular conjugated DPP derivative (EHTPPD‐ECPA) with cyano and alkyl groups exhibited high solubility in both polar and nonpolar solvents. Organic photodetectors with the EHTPPD‐ECPA material exhibited stable and durable sensing of strong near UV and visible lights, while the EHTPPD‐ECPA material contributed to the improved performance of organic solar cells with diffusion‐processed BHJ layers. The diffusion‐processed method showed the remarkably improved efficiency.